Criminal Law Analysis of Sexual Crimes against Children - Samsidar, Samsidar (PT. Anagata Sembagi Education, 2024)
Sexual crimes against children are crimes that have extraordinary impacts on victims, both physically, psychologically, and socially. Protection of children as the nation's next generation is a primary concern in the criminal law system in Indonesia. This article aims to analyze the application of criminal law to perpetrators of sexual crimes against children, by reviewing relevant laws and regulations such as Law Number 35 of 2014 concerning Child Protection and Law Number 17 of 2016 which regulates the increase in criminal sanctions for perpetrators. Through a normative legal approach, this article evaluates the extent to which these legal provisions are able to provide a deterrent effect, protect the rights of victims, and prevent the recurrence of similar crimes. The analysis found that although regulations have been strengthened, implementation in the field still faces challenges, such as difficult evidence processes and suboptimal victim protection. This article suggests the importance of synergy between law enforcers, child protection institutions, and the wider community in creating a comprehensive protection system for children from sexual crimes.